'As if "relations" mattered': a reply to Martin Weber. Issue 1 (2nd January 2014) - Davies,
Abstract : This is a reply to:Weber, Martin. 2014. "As if 'relations' mattered: how to subvert positional bias in social science with a lot of help from 'others'…." Global Discourse . 4 (1): 1–13. http://dx.doi.org/10.1080/23269995.2013.805513